BURST GALAXIES - Silich, S. A. (Одеські астрономічні публікації, 2017)
Here we present observational evidences and theoretical approaches to the starburst phenomena in the different types of the galaxies. A starburst model for AGN, large-scale gas outflow of the central regions of galaxies, and ultimate fate of a matter venting out of a starforming regions are discussed.